Surgical Management of Desmoid Tumors—Patient Selection, Timing, and Approach - Catherine Sarre Lazcano; Alessandro Gronchi (Current Oncology)
Desmoid tumors are rare, deep-seated myofibroblastic tumors with an unpredictable course, ranging from spontaneous regression to infiltrative growth and locally aggressive behavior, but without metastatic potential. Over the past few decades, advances in understanding their natural history, underlying molecular pathways, and patient care priorities have shifted the treatment paradigm from upfront surgical resection to initial active surveillance, with further treatment dictated by continuous disease progression or associated symptoms. However, there are still specific scenarios where surgery continues to play an important role in locoregional treatment and symptom control. This article will focus on current treatment strategies and surgical indications in adult patients with desmoid tumors, emphasizing patient selection, anatomic site-specific considerations, and surgical technique. Understanding the nuanced role of surgery within the growing treatment landscape is key for individualized patient care in a multidisciplinary setting to optimize quality of life and long-term outcomes.